DINAMIKA PENDIDIKAN ISLAM DAN PENDIDIKAN SEKULER: KAJIAN MENDALAM TENTANG RUANG LINGKUP, KARAKTERISTIK, DAN IMPLIKASINYA - Wulandari; Mirdad, Jamal; Julhadi; Saifullah; Asmaret, Desi (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Education is one of the key pillars of human civilization development, with two main educational systems prevailing: Islamic education and secular education. This study aims to analyze the dynamics between these two educational systems by exploring their scope, characteristics, and the implications they pose within the social, cultural, and intellectual contexts. This research adopts a qualitative approach with a descriptive-analytical method, examining various literatures, educational theories, and relevant empirical data. The findings reveal that Islamic education is characterized by spiritual values and the integration of religious knowledge with worldly sciences, whereas secular education emphasizes rationality, objectivity, and the separation of religion from science. These fundamental differences result in distinct educational goals, teaching methods, and academic paradigms. Furthermore, the study reveals that the challenges of globalization and modernization have prompted efforts to reform and integrate Islamic education to remain relevant in the face of changing times. On the other hand, secular education is gradually incorporating moral and ethical frameworks as a response to the value crisis in modern society. Therefore, this study highlights the need for synthesis or a more inclusive approach in building a holistic, balanced, and human-centered educational system.